Higher bone cement volume in total knee arthroplasty lowers the risk of postoperative radiolucent lines - Keintzel, Maximilian; Smolle, Maria A.; Staats, Kevin; Böhler, Christoph; Windhager, Reinhard; Koutp, Amir; Leithner, Andreas; Donner, Stefanie; Perka, Carsten; Reiner, Tobias; Renkawitz, Tobias; Leica, Alexandra; et al. (Knee surgery, sports traumatology, arthroscopy, 2025)
Purpose The aim of this multicenter study was to analyze the potential impact of patient demographics and cementation technique towards the development of radiolucent lines (RLLs) in primary total knee arthroplasty (TKA). It was hypothesized that cementation techniques, including higher cement volume, double-layer cementation technique and hardening in full extension, reduce RLL incidence by improving stability, whereas demographic factors such as age, BMI and smoking may increase RLL risk by affecting bone quality and mechanical loading. Methods Altogether, 776 patients (median age: 70.7 years; 39.2% males) underwent TKA at five tertiary orthopaedic centres between 11/2013 and 04/2023. X-rays were analyzed retrospectively for the evaluation of RLLs taken between 6 and 36 months from surgery. RLLs on anterior-posterior and lateral X-rays taken at a median of 14 months (range: 6-36) from primary surgery were evaluated using the Knee Society roentgenographic evaluation and scoring system. Potential associations of demographics and cementation technique on the occurrence of RLLs during follow-up were analyzed with uni- and multivariate logistic regression models. Results The overall incidence of RLLs around the TKA amounted to 37.4% (n = 290), with the tibial component (29.4%) being more commonly affected than the femoral component (15.0%). Patient age, gender, BMI and smoking habits were not significantly associated with higher incidence of RLLs (p > 0.05). The amount of cement used (odds ratio: 0.99; 95% confidence interval: 0.98-0.99; p = 0.028) was independently associated with a lower incidence of RLLs, irrespective of the double- versus single-layer cementation technique, cement hardening in full extension and time required for the X-ray. Conclusions No influence of demographic data on the incidence of RLL was found, yet specific cementation techniques appeared beneficial. Future studies with longer follow-up periods are required to provide further insight into the herein-made preliminary findings and to assess potential associations with long-term aseptic loosening rates. Level of Evidence Level III, retrospective observational study.